Rancang Bangun Inkubator Telur Berbasis IoT Dengan Sumber Daya Listrik Dari Panel Surya - Erik Agustian Yulanda (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The egg incubator functions to maintain the required temperature and humidity for hatching eggs. However, the lack of human involvement in monitoring can pose challenges in maintaining the appropriate incubation environment and affect embryo survival rates. Therefore, the objective of this research is to create an intelligent and sustainable solution for poultry egg incubation with precise temperature and humidity control, as well as optimizing the hatching process. The approach taken in this study involves combining IoT technology and renewable energy, namely solar panels. The incubator system is equipped with DHT22 sensors to measure temperature and air humidity inside the machine. Data from the DHT22 sensors are used to automatically adjust and control the temperature and humidity within the ideal range for embryo development. Additionally, the system includes a stepper motor that periodically rotates or tilts the egg trays to provide proper air circulation and even turning for better hatching results. Users can monitor and control the incubator's environmental conditions in real-time through the Blynk application accessible from mobile devices. The Blynk application offers an intuitive graphical interface, enabling users to remotely control the incubator's lights and fans according to their needs. Test results demonstrate the solar panel's effective performance in generating electricity, the successful functionality of the DHT22 sensor, providing accurate temperature and humidity information in the surrounding environment, and the reliable performance of the Blynk application as a remote control system for the incubator's lights and fans. Overall, the IoT-based incubator system utilizing solar panels, DHT22 sensors, and the Blynk application proves to be an innovative solution to enhance egg hatching efficiency, improve production outcomes, and contribute to environmental preservation.